Evolution of the metal hyperaccumulation and hypertolerance traits. (19th July 2020) - Manara, Anna; Fasani, Elisa; Furini, Antonella; DalCorso, Giovanni
Abstract: To succeed in life, living organisms have to adapt to the environmental issues to which they are subjected. Some plants, defined as hyperaccumulators, have adapted to metalliferous environments, acquiring the ability to tolerate and accommodate high amounts of toxic metal into their shoot, without showing symptoms of toxicity. The determinants for these traits and their mode of action have long been the subject of research, whose attention lately moved to the evolution of the hypertolerance and hyperaccumulation traits. Genetic evidence indicates that the evolution of both traits includes significant evolutionary events that result in species‐wide tolerant and accumulating backgrounds. Different edaphic environments are responsible for subsequent refinement, by local adaptive processes, leading to specific strategies and various degrees of hypertolerance and hyperaccumulation, which characterize metallicolous from non‐metallicolous ecotypes belonging to the same genetic unit. In this review, we overview the most updated concepts regarding the evolution of hyperaccumulation and hypertolerance, highlighting also the ecological context concerning the plant populations displaying this fascinating phenomenon. Abstract : Critical overview of the recent advances concerning the evolution of the hyperaccumulation and hypertolerance traits, which confer to certain plants, defined as hyperaccumulators, the ability to store substantial amounts of heavy metals into their shoots without suffering toxicity symptoms.